Developing an environmental monitoring system (EMS) and environmental monitoring plan (EMP) in the establishment of landfill post-closure procedure - Fatin Safwanah, Jamaruddin (Universiti Malaysia Perlis (UniMAP), 2013)
Access is limited to UniMAP community.